Judy Moody and Friends : Triple Pet Trouble - McDonald, Megan; Madrid, Erwin; Reynolds, Peter, 1961- (Somerville, Massachusetts : Candlewick Press, 2015)
Determined to help her sick pet Venus flytrap, Judy Moody enlists the aid of an unruly toad and a mind-reading cat to help her find a cure.
Keywords: Moody, Judy (Fictitious character) -- Juvenile fiction; Venus's flytrap -- Juvenile fiction; Toads as pets -- Juvenile fiction; Cats -- Juvenile fiction; Plant diseases -- Juvenile fiction; Pets -- Juvenile fiction; Moody, Judy (Fictitious character) -- Fiction; Venus's flytrap -- Fiction; Toads as pets -- Fiction; Cats -- Fiction; Plant diseases -- Fiction; Pets -- Fiction; Juvenile fiction